Subtractive genomic approach to uncover novel drug targets in Salmonella typhimurium and computational screening of food-based polyphenols as inhibitors - Valathoor, Mohammed Naveez; Venugopal, Subhashree; Rajan, Anand Prem (Frontiers in Bioinformatics, 2025)
IntroductionThe rise of multidrug-resistant Salmonella typhimurium is a severe public health threat that renders conventional antibiotics ineffective. This study employed a computational strategy to identify a novel drug target in S. typhimurium and screen food-based polyphenols as potential inhibitors.MethodsA subtractive genomics approach was used to identify essential, pathogen-specific proteins. A lead target was prioritized based on its druggability, localization, and network interactions. The target’s 3D structure was then modeled for molecular docking, molecular dynamics (MD) simulations, and binding free energy calculations with a polyphenol library.ResultsThe screening identified UDP-N-acetylglucosamine transferase (MurG) as a promising and previously unexplored drug target. The polyphenol 6-prenylnaringenin showed a superior binding affinity for MurG compared to the antibiotic ciprofloxacin. Subsequent MD simulations and binding free energy calculations confirmed that the MurG-6-prenylnaringenin complex was significantly more stable.ConclusionThis study validates MurG as a druggable target in S. typhimurium and identifies 6-prenylnaringenin as a potent inhibitor. With computational metrics superior to ciprofloxacin, 6-prenylnaringenin is a promising lead compound for developing new anti-Salmonella therapeutics. Future experimental validation is required to confirm these in silico findings.